Isolation, chemical and functional characterization of several new K+-channel blocking peptides from the venom of the scorpion Centruroides tecomanus. (1st June 2016) - Olamendi-Portugal, Timoteo; Bartok, Adam; Zamudio-Zuñiga, Fernando; Balajthy, Andras; Becerril, Baltazar; Panyi, Gyorgy; Possani, Lourival D.
Abstract: Six new peptides were isolated from the venom of the Mexican scorpion Centruroides tecomanus ; their primary structures were determined and the effects on ion channels were verified by patch-clamp experiments. Four are K + -channel blockers of the α-KTx family, containing 32 to 39 amino acid residues, cross-linked by three disulfide bonds. They all block Kv1.2 in nanomolar concentrations and show various degree of selectivity over Kv1.1, Kv1.3, Shaker and KCa3.1 channels. One peptide has 42 amino acids cross-linked by four disulfides; it blocks ERG-channels and belongs to the γ-KTx family. The sixth peptide has only 32 amino acid residues, three disulfide bonds and has no effect on the ion-channels assayed. It also does not have antimicrobial activity. Systematic numbers were assigned (time of elution on HPLC): α-KTx 10.4 (time 24.1); α-KTx 2.15 (time 26.2); α-KTx 2.16 (time 23.8); α-KTx 2.17 (time 26.7) and γ-KTx 1.9 (elution time 29.6). A partial proteomic analysis of the short chain basic peptides of this venom, which elutes on carboxy-methyl-cellulose column fractionation, is included. The pharmacological properties of the peptides described in this study may provide valuable tools for understanding the structure-function relationship of K + channel blocking scorpion toxins. Highlights: Four new peptides of the α-KTx family of scorpion venom components are described. A novel blocking peptide that blocks regular function of ERG-channels is reported. A 32 amino acid long peptide with no apparent pharmacological action on K + -channels was found. For the first time it is demonstrated that venom from Centruroides tecomanus also has peptides that block ion-channel function.